IMPROVEMENT OF SEI TUAN PERCUT CLAY SOIL STABILIZED WITH PALM HALL ASH USING LOADING TEST: PERBAIKAN TANAH LEMPUNG PERCUT SEI TUAN YANG DISTABILISASIKAN DENGAN ABU CANGKANG KELAPA SAWIT MENGGUNAKAN UJI LOADING TEST - Syamsul Bahri (LPPM UPMI, 2023)
In this research, several tests and preparations were carried out to obtain data to support completing this final assignment. The research was conducted at the UPMI Medan Pavement Materials Laboratory, Civil Engineering Department. Clay soil samples were taken in the Percut Village area, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province. In this soil sampling area, potholes and bumpy roads are often found. Soil was taken by digging to a depth of 1 meter. The sample is yellow-brown in color, physically the soil has a high water content. The weather at the time of sampling was hot. Work is carried out around 12.00 - 17.00 WIB. The main equipment settings are the settings carried out on the test tank and what is included in it, such as installing tarpaulin, pipe channels, and filling the test tank with clay mixed with coconut shell ash with variations of 0%, 6% and 9%. Installation of the tarpaulin is carried out carefully so that it does not leak, causing water in the clay soil mixed with coconut shell ash to seep through the existing holes. Likewise, filling the test tank with clay mixed with coconut shell ash. Based on the soil classification, the American Association of State Highway and Transportation Official Classification (AASHTO) system can be used to classify soil types. Meanwhile, based on the system data obtained from testing the physical properties of the soil in the form of soil that passes sieve No. 200 = 95.72% Based on the percentage value passing filter No. 200, the soil sample above has a percentage greater than 35% that passes the No. sieve. 200, then based on the AASHTO classification table it is grouped into A-7-5 which is a type of soil containing silt - clay. The elasticity of fine-grained soil is classified as silt if it has a plasticity index, PI <10 and is categorized as clay if it has a plasticity index, PI >11. The research results showed that the decrease due to the load on clay soil which did not use variations in the palm shell ash layer was 90 mm. The research results showed that the decrease due to the load on clay soil using a 6% palm shell ash layer variation was 160 mm. The research results showed that the reduction due to the load on clay soil using a 9% palm shell ash layer variation was 90 mm